PERENCANAAN PAJAK MELALUI REVALUASI ASET STUDI KASUS DI HOTEL WISATA INDAH - Agung Nurmansyah (Universitas Sahid Surakarta, 2017)
The Government on October 15, 2015 issued the economic package to V, one of which is about the revaluation of fxed assets. Tax facilities that can be used for the taxation of one of them is the revaluation of fxed assets. Implementation of tax planning with case study in Hotel Wisata Indah Surakarta with data of 2015. The method used is to analyze tax data, see tax data that may implemented tax planning, the implementation of tax planning and tax taxpayer update. In this case study can make tax savings of Rp. 3.900.000 or a tax reduction of 85 percent.